2019
DOI: 10.1177/2050640619858211
|View full text |Cite
|
Sign up to set email alerts
|

Palliative chemotherapy for patients with synchronous metastases of small‐bowel adenocarcinoma: A reflection of daily practice

Abstract: Background As small-bowel adenocarcinoma (SBA) is scarce, no standard systemic regimen in metastatic disease has been defined. Objective To obtain insights into the use and effects of palliative chemotherapy in patients with metastatic SBA in a population-based setting. Methods Data from the Netherlands Cancer Registry of patients with metastatic SBA between 2007 and 2016 were used ( n = 522). For patients treated with palliative chemotherapy, differences in treatment regimens and survival were evaluated. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…After full-text revision, 57 studies were included, with a total of 35 176 patients. Among the 57 studies, 6 studies 27 , 28 , 29 , 30 , 31 , 32 were prospective cohort studies or phase 2 trials, and 51 studies 1 , 3 , 4 , 17 , 19 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 were retrospective in nature ( Table ; eTables 1 and 2 in…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After full-text revision, 57 studies were included, with a total of 35 176 patients. Among the 57 studies, 6 studies 27 , 28 , 29 , 30 , 31 , 32 were prospective cohort studies or phase 2 trials, and 51 studies 1 , 3 , 4 , 17 , 19 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 were retrospective in nature ( Table ; eTables 1 and 2 in…”
Section: Resultsmentioning
confidence: 99%
“…Of 57 studies, 23 studies 3 , 17 , 27 , 29 , 30 , 31 , 32 , 33 , 36 , 38 , 44 , 49 , 50 , 51 , 58 , 60 , 62 , 63 , 70 , 71 , 73 , 74 , 77 (40.4%) were subject to serious risk of bias due to the lack of multivariable analyses and selection bias (eTable 3 in Supplement 1 ). Thirty-three studies 1 , 4 , 19 , 28 , 34 , 35 , 37 , 39 , 40 , 41 , 42 , 43 , 45 , 46 , 47 , 48 , 52 , 53 , 54 , 55 , 56 , 57 , 59 , 61 , 64 , 65 , 66 , 67 , 69 , 72 , 75 , 76 , 78 (57.9%) had medium or low risk of bias. For 1 study, 68 risk of bi...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic review of seven prospective studies revealed that adjuvant chemotherapy was effective for unresectable or metastatic SBA ( 34 ). In a retrospective analysis of patients with metastatic SBA, patients who received palliative chemotherapy had a median OS of 9.3 months, significantly better than those who did not receive chemotherapy ( 35 ). These studies suggested that adjuvant chemotherapy had a certain benefit in improving the prognosis of metastatic SBA.…”
Section: Discussionmentioning
confidence: 99%